Radical Releasing Anti-tuberculosis Agents and the Treatment of Mycobacterial Tuberculosis Infections - An Overview - Kareem, Afeez I.; Malan, Sarel F.; Joubert, Jacques (Mini Reviews in Medicinal Chemistry, 2022)
Abstract: The treatment and management of tuberculosis (TB) is a major global concern. Approved drugs for the treatment of TB, to date, have displayed various modes of action which can be grouped into radical releasing and non-radical releasing anti-TB agents. Radical releasing agents are of special interest because they diffuse directly into the mycobacterium cell wall, interact with the host cell DNA, causing DNA strand breakages and fatal destabilization of the DNA helix inhibiting nucleic acid synthase. As a therapeutic agent with the aforementioned activity, nitroimidazoles and most especially bicyclic nitroimidazoles are currently in clinical use for the treatment of tuberculosis. However, the approved drugs, pretomanid (PR) and delamanid (DE) are limited in their nitric oxide radical (NO•) releasing abilities to cause effective bactericidity. It is believed that their bactericidal activity can be improved by harnessing alternative strategies to increase NO• release. The last decade has witnessed the strategic inclusion of NO-donors into native drugs to improve their activities and/or reverse resistance. The rationale behind this strategy is the targeting of NO• release at specific therapeutic sites. This review, therefore, aims to highlight various radical releasing agents that may be effective in the treatment of TB. The review also investigates various structural modifications to PR and DE and suggests alternative strategies to improve NO•release as well as some applications where NO-donor hybrid drugs have been used with good therapeutic effect.
Keywords: Mycobacterium tuberculosis